Unleashing the Power of User-Generated Content: Emphasize the significance of UGC in the co-creation of destination marketing strategies - Li,Yuxin; Gu,Lingxuan (2024)
Research Aim This thesis explores the role of user-generated content (UGC) in destination marketing, specifically focusing on Harbin, China. It aims to understand how UGC on social media, particularly Douyin, influences Harbin's destination image and the motivations behind content creation. Methodology A mixed-method approach was employed, combining netnography and semi-structured interviews. The netnography involved observing behaviors and content related to Harbin tourism on Douyin. Semi-structured interviews were conducted with young travelers who visited Harbin between 2023 and May 2024. Findings The findings indicate that UGC significantly enhances Harbin's destination image by showcasing travel ease, local authenticity, and friendliness. Douyin's features, such as comments and hashtags, facilitate extensive user engagement, which helps shape Harbin’s image. The motivations for creating UGC include expertise, consumer capital, time, experiential benefits, self-worth, and status. Research Implications The theoretical contributions of this research expand the framework of consumer co-creation motivations and highlight the role of UGC in destination marketing. Practically, the study offers recommendations for Destination Marketing Organizations (DMOs) on leveraging UGC and forming strategic platform partnerships. Future research should consider larger sample sizes, exploring various social media platforms, and examining different cultural contexts.
Keywords: User-generated content (UGC); destination image; Harbin; Douyin; co-creation; social media; destination marketing